Cosmology, calendars, and horizon-based astronomy in ancient Mesoamerica - Dowd, Anne S., editor; Milbrath, Susan, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2015)
This book is an interdisciplinary tour-de-force that establishes the critical role astronomy played in the religious and civic lives of the ancient peoples of Mesoamerica. Providing examples of how pre-Columbian peoples merged ideas about the cosmos with those concerning calendar and astronomy, and showcases the value of detailed examinations of astronomical data for understanding ancient cultures.--Provided by publisher.
Part I. Introduction -- 1. An Interdisciplinary Approach to Cosmology, Calendars, and Horizon-Based Astronomy / Susan Milbrath, Anne S. Dowd -- Part II. Horizon-Based Astronomy -- 2. Pyramids Marking Time: Anthony F. Aveni's Contribution to the Study of Astronomical Alignments in Mesoamerican Architecture / Ivan Šprajc -- 3. Maya Architectural Hierophanies / Anne S. Dowd -- 4. Mountain of Sustenance: Site Organization at Dainzu-Macuilxochitl and Mesoamerican Concepts of Space and Time / Ronald K. Faulseit -- Part III. Cosmological Principles -- 5. The North Celestial Pole in Ancient Mesoamerica / Clemency Coggins -- 6. A Seasonal Calendar in the Codex Borgia / Susan Milbrath -- 7. Iconography and Metaphorical Expressions Pertaining to Eclipses: A Perspective from Postclassic and Colonial Maya Manuscripts / Gabrielle Vail -- 8. The Maya Deluge Myth and Dresden Codex Page 74: Not the End but the Eternal Regeneration of the World / John B. Carlson -- Part IV. Calendar Records -- 9. The Ancient Maya Moon: Calendar and Character / Flora Simmons Clancy -- 10. Pecked Circles and Divining Boards: Calculating Instruments in Ancient Mesoamerica / David A. Freidel, Michelle Rich -- 11. The "Las Bocas Mosaic" and Mesoamerican Astro-Calendrics: "Calculator" or Hoax? / Prudence M. Rice -- 12. Some Alternative Eclipse Periodicities in Maya Codices / Victoria R. Bricker, Harvey M. Bricker -- 13. Modeling Indigenous Mesoamerican Eclipse Theory / John Justeson -- Part V. Conclusion -- 14. Maya Books and Buildings at Baktun's End / Anthony F. Aveni.
Keywords: Indian calendar; Archaeoastronomy; Aztec astronomy; Maya astronomy